Influence of Essential Oils on Inhibiting Biogenic Amine-Producing Bacteria in Xinjiang Smoked Horsemeat Sausage - Ruiting Li; Fanfan Zhang; Shiling Lu (Fermentation)
(1) Background: Xinjiang smoked horsemeat sausage is a popular food; however, bio-genic amine (BA) production is a concern for food safety. (2) Methods: the present study selected the three most toxic BAs for food safety (histamine, tyramine, and putrescine) and determined the bacteria that produce them. (3) Results: After 24 h of incubation, fifteen isolated strains, especially Enterobacter ludwigii MT705841 and Enterobacter bugandensis MT705832 produced putrescine (485.52 μg/mL and 408.95 μg/mL, respectively, p < 0.05); eight isolated strains, especially Proteus vulgaris MT705833 and Bacillus subtilis MT705839 produced histamine (63.86 μg/mL and 30.40 μg/mL, respectively, p < 0.05); and 14 isolated strains, especially Staphylococcus saprophyticus MT705831 and Proteus penneri MT705835 produced tyramine (482.26 μg/mL and 497.76 μg/mL, respectively, p > 0.05). Artemisia oil moderately inhibited P. vulgaris MT705833 and B. subtilis MT705839 after 48 h of in vitro incubation, decreasing histamine production by 44.83% and 47.92% for these two bacteria after 24 h and 20 h of incubation, respectively. Cinnamon oil strongly inhibited putrescine production by E. bugandensis MT705832 and E. ludwigii MT705841, decreasing production by 96.63% and 92.03% for these two bacteria after 24 h of incubation, respectively. Grapeseed oil slightly inhibited P. penneri MT705835 tyramine production (only after 4 h of incubation) and had an unstable inhibitory effect on Citrobacter freundii MT705836 tyramine production. (4) Conclusions: the results of this study suggest that cinnamon oil can be an effective food additive for the prevention of BA production in Xinjiang smoked sausages.